PROFIL PERESEPAN OBAT ANTI TUBERKULOSIS PADA PASIEN ANAK DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT X BOGOR PERIODE JANUARI – MARET 2023 - Dewantoro, Agung; Andriati, Riris; Haryani, Setianti; Sakinah, Nur; Dewi, Bheta Sari; Rahajeng, Suny Koswara; Ismaya, Nurwulan Adi (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2023)
Childhood tuberculosis is a disease caused by Mycobacterium tuberculosis at the age of 0-11 years. In Indonesia, tuberculosis is the third leading cause of death after cardiovascular disease and respiratory disease in all age groups. Tuberculosis in children is the most important factor in developing countries because the number of children aged 15 years is 40-50% of the total population. Objective: To find out the Prescribing Profile of Anti-Tuberculosis Drugs in Pediatric Patients at the Bogor X Hospital Outpatient Pharmacy Installation for the January – March 2023 period. Methods: The type of research conducted was a non-experimental study with a descriptive research design. This research method was carried out using a quantitative approach and retrospective data collection. The retrospective approach is a study that looks backwards, which means collecting data from medical records with a diagnosis of tuberculosis. Results: This study showed that of the 94 tuberculosis patients at Bogor X Hospital, the dominant sex was male (55.4%), with an age range of 0-5 years (65.9%), with an anatomical location of the disease in pulmonary tuberculosis (91.4%), with treatment for 6 months (95.7%) with comorbid dyspepsia (29.6%), with an intensive treatment phase, namely anti-tuberculosis drugs (66%), with an advanced treatment phase, namely anti-tuberculosis drugs (72.8%) and the use of other drugs, namely vitamins (72.8%).